NEUTRONIC ANALYSIS OF TRIGA 2000 CORE RESHUFFLING SCENARIO BASED ON U-235 BURNUP MASS - Fadhilla Kusumawardhani, Tiara
Reactor TRIGA 2000 Bandung has been utilized in various fields since 1965. In order to ensure a safe and optimum operation of the reactor, core management is needed, including specification of fuel assembly loading and reshuffling patterns. TRIGA 2000 core management has to comply safety parameters stated in Operating Limit and Condition (OLC). In this study, neutronic analysis of several TRIGA 2000 reactor core reshuffling patterns were done using MCNP. The neutronic aspects evaluated were effective multiplication factor, reactivity, and power peaking factor. After the optimum pattern was obtained, operation simulation was run to determine the operating length until the core reaches subcritical state. Fuel reshuffling patterns were arranged based on variation of number of each fuel types, variation of fuel positions with different uranium-235 concentration, and empty slot positioning variations. The variation of number of each IXHOW\SHVGLGQ¶WUHVXOWLQVLJQLILFDQWFKDQJH in calculated neutronic aspects. Meanwhile, fuels with lower uranium-235 concentration should be placed in the center of the core starting with fuels with high burnup mass so power flattening can be achieved. Empty slot positioning in inner ring results in lower effective multiplication factor. The optimum scenario that fulfills OLC was Scenario 3 arranged with empty slot in ring D. Effective multiplication factor 1.010, axial power peaking factor 1.208, and radial power peaking factor 1.559 were achieved with 90 days operation time until the core reaches subcritical state